Enhanced Surgeons: Understanding the Design of Augmented Reality Instructions for Keyhole Surgery - Davis, Christoph; Yoo, Soojeong; Clarkson, Matthew J.; Thompson, Stephen (2023 IEEE Conference on Virtual Reality and 3D User Interfaces Abstracts and Workshops (VRW), 2023)
It is important to understand how to design AR content for surgical contexts to mitigate the risk of distracting the surgeons. In this work, we test information overlays for AR guidance during keyhole surgery. We performed a preliminary evaluation of a prototype, focusing on the effects of colour, opacity, and information representation. Our work contributes insights into the design of AR guidance in surgery settings and a foundation for future research on visualisation design for surgical AR.